BIBLIOMETRIC ANALYSIS OF THE TERM GAME-BASED LEARNING IN EARLY CHILDHOOD STUDIES - Nurlaeli Fitriah; Luthfiya Fathi Pusposari; Lusty Firmantika; Ainur Rochmah; Ika Siti Rukmana (-, 2022)
Game-based learning is a learning model that motivates and is believed to improve various aspects of student development. GBL has become a study that has begun to be of great interest to researchers. However, game-based learning applied to early childhood education has not been widely practised. This study aims to provide an extensive bibliometric review of game-based learning in early childhood. Articles were searched using the scopus.com database, and 428 articles were captured. After screening with inclusion and exclusion criteria, 256 articles were deemed eligible. The results of the study indicate that through the resulting bibliometric map, it can be seen that the opportunity to study game-based learning in early childhood studies is very prospective, especially those related to human-computer interaction.